Pengaruh Kemampuan, Penempatan Dan Fasilitas Kerja Terhadap Efektivitas Kerja Pegawainegeri Sipil Pada Bidang Sosial Budayaba Dan Perencanaan Pembangunan Daerah (BAPPEDA) Kabupaten Kutai Kartanegara - Hamid, Akhmad Sofyan (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2008)
At Bappeda  Social culture  sub area Kutai Kartanegara Regency, where the effectiveness of the employee haven’t optimal yet the same manner as necessary. It is marked with the appearance of the problem where the employees start lazy to work. There are some employees that rarely come to work or seldom in the office when the job hasn’t finished, they just let the task floated. the task that should be finished in 2 days ,just finished in one week etc.  Key Word : Location, Facility,  Effectiveness